Intoxication by Astragalus garbancillo var. garbancillo in llamas - Marín, Raúl Eduardo (2020)
Lysosomal storage diseases are inherited and acquired disorders characterized by dysfunctional lysosomes. Intracytoplasmic accumulation of undegraded substrates leads to impaired cellular function and death. Several plant species are toxic to livestock because of the presence of indolizidine alkaloids, including swainsonine, which cause a storage disease. Swainsonine-induced nervous disease (i.e., locoism) of sheep and cattle is well recognized in several parts of the world, particularly in the western United States and in parts of Australia. Spontaneous intoxication by Astragalus garbancillo var. garbancillo was suspected in a group of 70 llamas (Lama glama) in Jujuy Province, northwestern Argentina. The animals grazed an area dominated by stands of A. garbancillo var. garbancillo. Clinical signs were staggering, ataxia, hypermetria, and progressive weight loss. The clinical course in individual animals was ~50 d. The main microscopic changes were Purkinje cell degeneration, necrosis, and loss, associated with intracytoplasmic vacuolation, meganeurite formation, and Wallerian degeneration. Specific positive labeling for ubiquitin was observed in axonal spheroids. Composite leaf and stem samples of A. garbancillo var. garbancillo analyzed by high-performance liquid chromatography contained 0.03% swainsonine. Based on the microscopic lesions, clinical history, and plant analysis, a diagnosis was made of storage disease caused by consumption of swainsonine-containing A. garbancillo var. garbancillo.